FARMER EMPOWERMENT INNOVATION IN RURAL IRRIGATION MANAGEMENT - Siska Fiyana, Bidiyah (Prospect Publishing, 2025)
Effective water resources management is a crucial challenge in rural Indonesia, especially in the context of climate change and increasing water demand for agriculture. This research examines the process of community empowerment through the Jogo Toya Kamulyan Irrigation Volunteer Forum (FRI) in the downstream area of the Pusur Sub-watershed, Klaten District, Central Java. The research objective is to analyze how the integration of the Support for Participatory Research and Popular Education (SPRE) and Volunteer Effort and Movements (VEM) approaches in the empowerment process of the Jogo Toya Kamulyan Irrigation Volunteer Forum (FRI) contributes to increasing community participation and the effectiveness of irrigation water resources management in the downstream area of the Pusur Sub-watershed. The research applied qualitative methods through in-depth interviews, participatory observation, and document analysis. The main findings showed that FRI Jogo Toya Kamulyan successfully established a participatory irrigation management system involving farmers, youth, and women from seven villages. This success is reflected in the normalization of irrigation channels, the development of a transparent water sharing system, and the adoption of technology through the SIBARI application. Interestingly, this study reveals how a grassroots initiative can transform into a water resources management model recognized by the local government, marked by FRI's joining the District Irrigation Commission. This study provides unique insights into the potential of community empowerment in addressing natural resource management challenges, and highlights the importance of multi-stakeholder collaboration and community-based innovation in sustainable rural development.